RETRACTED: Mechanosensitive channel candidate MCA2 is involved in touch-induced root responses in Arabidopsis - Nakano, Masataka; Samejima, Rika; Iida, Hidetoshi (Frontiers in Plant Science, 2014)
The Ca2+-permeable mechanosensitive (MS) channel is a mechanical stress sensor. We previously reported that Arabidopsis MCA1 and its paralog MCA2 functioned individually as Ca2+-permeable mechanosensitive (MS) channels. In the present study, we showed that the primary roots of the mca2-null mutant behaved abnormally on the surface of hard medium. First, primary roots are known to exhibit a skewing growth pattern on the surface of vertically placed agar medium. On such surface, the primary roots of mca2-null skewed more than those of the wild type. Second, when seedlings were grown on a tilted agar surface, the primary root of mca2-null showed abnormal waving patterns. Third, wild-type seedlings eventually died when grown on horizontally placed 3.2% gelrite medium, which was too hard to allow the primary roots of the wild type to penetrate, because their primary roots sprang from the surface of the medium and may not have been unable to absorb water and nutrients. In contrast, the primary roots of mca2-null, but not those of mca1-null, were able to creep over the surface of the medium and grow. Fourth, when grown on the surface of 3.2% agar medium supplemented with 30 mM CaCl2, only mca2-null grew with a root that coiled in a clockwise direction. Lastly, on the surface of vertically placed rectangular plates that allowed primary roots to grow vertically down to the frame of the plate, wild-type primary roots grew horizontally after touching the frame at an angle of 90˚. During the horizontal growth, only the extreme root tips maintained contact with the frame. In contrast, the primary roots of mca2-null allowed not only the extreme root tips, but also the meristem and elongation zones to maintain contact with the frame during horizontal growth. These results suggest that MCA2 is involved in touch-related root responses.